PENGARUH PEMBELAJARAN KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA PADA SISWA KELAS XI SMK BATIK 2 SURAKARTA - -, Ida Dwi Suryaningrum -; -, Dewi Kusuma Wardani -; -, Muhammad Sabandi - (Pendidikan Ekonomi Bidang Keahlian Khusus Tata Niaga FKIP Universitas Sebelas Maret, 2016)
This research aims to test the influences entrepreneurship-learning factor toward attitudes toward the behavior, subjective norms, dan perceived behavioral control on students; family-environment factor toward attitudes toward the behavior, subjective norms, and perceived behavioral control on students; and attitudes toward the behavior, subjective norms, and perceived behavioral control toward the entrepreneurial interest on students. The population of this research is all XI-grade students in SMK Batik 2 Surakarta which the total is 189 students. The sample of this research is 100 students chosen by the technique simple random sampling based on lottery. The results of this research are there is a positive and significant influence between entrepreneurship learning and attitude toward, subjective norms, perceived behaviour control; there is a positive and significant influence between family environment and attitude toward the behavior; subjective norms, perceived behavior control; there is a positive and significant influence between attitude toward the behavior, subjective norms, perceived behavior control and the entrepreneurial interest.